Efektivitas Pengelolaan Sampah Pada Pasar Modern Adaro Paringin Kabupaten Balangan - Selamat Riadi; Riswandi Ahdiat; Haji Mukti Ramadhani (Program Magister Ilmu Administrasi Bisnis FISIP Universitas Lambung Mangkurat, 2025)
Abstract: Waste Management Efforts at the Adaro Paringin Modern Market, Balangan Regency, the problem is the lack of monitoring in waste management, the lack of trash bins available in the market and the lack of field workers which causes it to be unable to reach a wider area. The purpose of this study was to determine the effectiveness of waste management at the Adaro Paringin Modern Market in Balangan Regency and the factors that influence it. This research uses a qualitative approach with a qualitative descriptive type. Data collection techniques used are interviews, observation and documentation. Data sources were taken by means of snowball sampling, totaling 17 people. After the data is collected, it is then analyzed using data reduction techniques, data presentation, and data verification or conclusion drawing. Testing the credibility of the data on this data extension extends the time of the researcher's participation in the field, observation persistence, triangulation according to the rules, checking with other members of the group, analyzing negative cases, and using the right references. The results of the research on the Effectiveness of Waste Management at the Adaro Paringin Modern Market, Balangan Regency, have not been effective. This can be seen from the indicators, namely first, the Achievement of Goals has been effective where the UPT is carrying out a clean market program, UPT officers and employees are running the program. Second, the quality of work has not been effective where there are still some that are not in accordance with the SOP and also do not do waste segregation. Third, the quantity of work has not been effective where the officers carry out their work well but there is still a shortage of cleaning staff. Fourth, timeliness has not been effective where the officers have carried out their duties according to the set time but do not know the garbage collection officers and the garbage transportation schedule that has been given has not been fully implemented. Fifth, job satisfaction has not been effective where socialization has been carried out but there are still some traders who do not participate and traders still feel uncomfortable.